Study on Optical Properties of Tin Oxide Thin Film at Different Annealing Temperature - Baco, Saturi; Chik, Abdullah; Md. Yassin, Fouziah (Journal of Science and Technology, 2012)
Tin Oxide (SnO2) thin film is one of the important transparent conducting oxides (TCOs) and applied in various fields such as in solar cells, optoelectronic devices, heat mirror, gas sensors, etc due to its electrical and optical transparency in visible light spectrum. In this paper, we presented the optical properties of tin oxide thin film at four different annealing temperatures (373 K, 437 K, 573 K and 673 K) prepared by radio frequency sputtering technique. The optical characteristic of these films was investigated using the UV-VIS 3101-PC Spectrophotometer. From this study, all samples exhibit high transmittance more than 70% in the visible light spectrum. Sample annealed at 473 K shows the maximum transmittance which is 87%. Refractive index, n were in the range of 2.33 – 2.80 at ï¬ = 550 nm and enhanced with the annealing temperature. However the extinction of coefficient, k was found to be very small. The optical band-edge absorption coefficients were found in the range of 104 – 105cm-1. The energy gap value was decreased with increasing annealing temperature and the type of photon transition was allowed direct transition.